Business Sustainability of Micro Enterprises in Selected Barangays of Taguig City: Basis for Enhanced Promotional Campaign - Tadia, Macario (International Journal of Sustainability and Advanced Integrated Research, 2026)
Micro enterprises play a crucial role in local economies, providing livelihoods and fostering community development. This study examines the business sustainability of micro enterprises in selected barangays of Taguig City, focusing on their challenges, resilience strategies, and the potential for enhanced promotional campaigns. Through surveys and interviews, the research identifies key factors influencing sustainability, including monetary management, customer retention, market competition, and government support. Findings indicate that micro enterprises struggle with a limited resources and fluctuating demand, necessitating adaptive business strategies. Additionally, effective promotional campaigns tailored to their specific needs can enhance visibility, attract customers, and strengthen sustainability. The study proposes a campaign for promotional enhancements that align with the micro enterprises’ operational capabilities and a market dynamic. The recommendations emphasize digital marketing, community engagement, and collaborative partnerships as essential tools for growth. This research contributes to the broader discourse on microenterprise sustainability, offering actionable insights for entrepreneurs, policymakers, and local stakeholders committed to economic resilience and business development.